2013
DOI: 10.1149/2.016312jes
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-Reverse Electrodeposition of Cu for the Fabrication of Metal Interconnection

Abstract: Superfilling and the leveling of Cu electrodeposition have relevance to the adsorption of organic additives and the changes in their surface coverage. In Part I of this study, it is observed that pulse-reverse electrodeposition changes the surface coverage of PEG-Cl − and SPS, by the anodic step. This implies that the performances of superfilling, as well as leveling, can be affected by pulse-reverse electrodeposition. In this research, the influences of pulse-reverse electrodeposition on both superfilling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Further, the impurities cause grain growth resulting in deteriorated mechanical properties, while also posing environmental concerns . Therefore, 'the required properties can be achieved by pulse reverse electrodeposition (PRED), in which the cathodic and reverse/anodic pulse parameters influence the texture, grain size, and type of grain boundaries. , PRED has several advantages in that it (1) reduces the usage of additives, (2) refines grain size, (3) improves properties because of the lower residual stress, (4) minimizes impurities in the deposit, and (5) reduces adsorption of hydrogen species and results in less surface roughness versus that of the foils prepared by DC and PED. , Therefore, PRED can be a viable option for controlling the texture, refining the grain size and the type of grain boundaries, which is the main focus of this study. However, very limited work has been done on the use of PRED for controlling crystallographic orientations in copper, suggesting that no correlation has been made so far between the processing parameters and the properties of as-deposited copper.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the impurities cause grain growth resulting in deteriorated mechanical properties, while also posing environmental concerns . Therefore, 'the required properties can be achieved by pulse reverse electrodeposition (PRED), in which the cathodic and reverse/anodic pulse parameters influence the texture, grain size, and type of grain boundaries. , PRED has several advantages in that it (1) reduces the usage of additives, (2) refines grain size, (3) improves properties because of the lower residual stress, (4) minimizes impurities in the deposit, and (5) reduces adsorption of hydrogen species and results in less surface roughness versus that of the foils prepared by DC and PED. , Therefore, PRED can be a viable option for controlling the texture, refining the grain size and the type of grain boundaries, which is the main focus of this study. However, very limited work has been done on the use of PRED for controlling crystallographic orientations in copper, suggesting that no correlation has been made so far between the processing parameters and the properties of as-deposited copper.…”
Section: Introductionmentioning
confidence: 99%
“…The organic additives, which strongly interact with both the Cu surface and each other, preferentially promote the electrodeposition rate at the bottom of the feature being filled, leading to superfilling. [14][15][16][17][18] Different additives elicit different effects on the reduction rate of Cu, and can therefore be categorized as either suppressors or accelerators. The particular combination of accelerators and suppressors generally preferred for Cu superfilling consists of bis(3-sulfopropyl) disulfide (SPS) and polyethylene glycol (PEG) in the presence of chloride ion (Cl − ).…”
mentioning
confidence: 99%
“…The previous studies have shown that the adsorption of SPS was closely associated with the chloride ions. 11,22,23,28,29 When the Cl − was added, a stable cuprous complex of CuCl would be formed on the surface, which was the preferential site for the adsorption of the SPS, forming a complex derivative of Cu-SPS-Cl − . The SPS could also directly adsorb on the sites of cuprous ions to form Cu + -SPS specie.…”
Section: Chloride Ion Dependent Adsorption Mechanism Of Single Peg An...mentioning
confidence: 99%
“…Hayase et al 20,21 reported that the reverse pulse could remove accelerator from copper z E-mail: qszhu@imr.ac.cn; xzhang14s@imr.ac.cn; czliu@sau.edu.cn surface with strong agitation and was helpful for a bottom-up filling of TSV using a Cu electrolyte with PEG-JGB-SPS additive system. Kim et al 22,23 reported that the anodic step promoted the displacement of PEG-Cl − by SPS at the early stage of electrodeposition and improved both superfilling and leveling performances. However, up to date, the operating mechanism of reverse pulse on the additive adsorption within the microvia is still unclear.…”
mentioning
confidence: 99%